PENGARUH PUPUK ORGANOTRIBA DAN NPK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt) DI LAHAN GAMBUT - Gemilang Andaru Indra Dewa; Jurnawaty Sjofjan; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research aimed to examine the interaction of fertilizer and NPK organotriba in peat on the growth and yield of sweet corn as well as getting the best dose. Research has been carried out in the garden Experiment Riau University Faculty of Agriculture of the month of February until May 2016. This study used a randomized block design in the form of factorial consisting of two factors. The first factor is fertilizer organotriba consists of 5 levels without organotriba, 2,5 ton/ha, 5 ton/ha, 7,5 ton/ha and 10 ton/ha. The second factor is a 16:16:16 NPK fertilizer which consists of three levels without NPK, 150 kg/ha and 300 kg/ha, two factors combined to obtain 15 combined treatment and the respective foreign re-treatment at 3 times, in order to obtain 45 experimental units. Each experimental unit consisted of 32 plants, six plants sampled. Data were analyzed statistically and continued using DNMRT at 5% parameters measured were the rate of plant growth, leaf area, the ratio of editorial roots, dry weight of plant, time appear male flowers and time appear female flowers, harvesting, production per plot, heavy with the husk, weight without husk, diameter and length of the cob plant sweet corn, data results showed that administration of organotriba dose of 10 ton/ha and NPK fertilizer dose of 300 kg/ha produce weight of 10,7 ton/ha higher than that of the untreated is 2,05 ton /ha  Keywords: sweet corn, Peatland, Fertilizers Organotriba